Pengaruh Penerapan Keselamatan Dan Kesehatan Kerja Terhadap Produktivitas Kerja Pegawai PT Sarana Pembangunan Palembang Jaya Unit Usaha Minyak Dan Gas Kota Palembang - Indah Mawarni; Zein Ghozali; Aras Tulip; Tutik Pebrianti; Vivin Afini (JURNAL EKOBIS Kajian Ekonomi dan Bisnis, 2019)
This study aims to determine the effect of implementation of occupational health and safety on employee work productivity in the Oil and Gas Business Unit of PT Sarana Pembangunan Palembang Jaya in Palembang. The population in this study are all employees in the Oil and Gas Business Unit of PT. Sarana Pembangunan Palembang Jaya, i.e. 47 people. The sample uses Isaac and Michael table formula with an error rate of 5%, the sample taken is 40 employees. The analytical method used is Product Moment Correlation analysis and multiple correlation. The results of testing the hypothesis show that there is a significant and positive effect between Work Safety on Employee Work Productivity, then there is a significant and positive effect between Occupational Health on Work Productivity, and Occupational health and safety have a positive and significant effect on the Employee Work Productivity variable. Suggestions from the author to PT. Sarana Pembangunan Palembang Jaya, Oil and Gas Business Unit on work safety, it is preferably that workers must comply with the working procedure and is expected to workers use safety equipment at work such as mask to protect the respiratory organs in order to avoid dust, helmet safety to protect in order to avoid falling items, safety shoes to protect the feet from sharp objects and others. With the PPE, employees can work safely and avoid work accidents in order to increase work productivity. In occupational health, first aid is provided, such as plaster for wounds, iodine, bandages and others.